2018
DOI: 10.1007/s10337-018-3555-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Characterization of Degradation Products of Dihydralazine and Hydrochlorothiazide in Binary Mixture by HPLC-UV, LC-DAD and LC–MS Methods

Abstract: Dihydralazine and hydrochlorothiazide were stored at high temperature and humidity, under UV/Vis light and different pH, as individual drugs and the mixture. Then, a sensitive and selective HPLC-UV method was developed for simultaneous determination of dihydralazine and hydrochlorothiazide in presence of their degradation products. Finally, the degradation products were characterized through LC-DAD and LC–MS methods. Dihydralazine was sensitive to high temperature and humidity, UV/Vis light and pH ≥ 7. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…So, we concluded for a second time that dihydralazine fragmented by loss of hydrazine and breaking phenazine ring. 16 In our LC-MS studies, products of m/z 121.03 and 161.04 were detected aer degradation in buffer of pH 10 and under UV/VIS light (in a solid state and in methanolic solutions). They were identied as phenylmethylhydrazine and 1hydrazinophthalazine.…”
Section: Identication Of Degradation Products By Lc-ms Methodsmentioning
confidence: 74%
See 3 more Smart Citations
“…So, we concluded for a second time that dihydralazine fragmented by loss of hydrazine and breaking phenazine ring. 16 In our LC-MS studies, products of m/z 121.03 and 161.04 were detected aer degradation in buffer of pH 10 and under UV/VIS light (in a solid state and in methanolic solutions). They were identied as phenylmethylhydrazine and 1hydrazinophthalazine.…”
Section: Identication Of Degradation Products By Lc-ms Methodsmentioning
confidence: 74%
“…phenylmethylhydrazine and 4dihydrazinylidenophthalazine were described for the rst time in our last paper. 16 When the stressed mixtures of indapamide and dihydralazine were examined, fragment ions of m/z 121.03, 161.04 and 187.04 from dihydralazine (aer degradation in borate buffer of pH 10, 1 M NaOH and under UV/VIS light), as well as of m/z 362.04 from indapamide (aer degradation in all conditions) were detected. In addition, quite new product of degradation of indapamide was detected as a fragment ion of m/z 232.98, as a result of degradation in 1 M HCl, borate buffer of pH 10 and under UV/VIS light (in solid state and in methanolic solution).…”
Section: Identication Of Degradation Products By Lc-ms Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of HCTZ, studies reveal that hydrolysis led to degradation product identified as 4-amino-6-chlorobenzene-1,3disulfonamide and formaldehyde [13][14][15][16]. Although various by-products are later identified during thiazide hydrolysis [17,18], isolation and full characterization of all degradation products were not reported at all. Qun Xu have proposed a plausible hydrolysis pathway of benzothiadiazine under thermal and humidity conditions showing various intermediates [19].…”
Section: Introductionmentioning
confidence: 99%